The Influence of Generation Z’s Social Media Activity in Jambi City on Stock Market Trends: A Statistical Analysis - Fatan Heti Anggraini; Sri Wahyu Ningsih; Muetia Apriliani; Akmalun Nisa; Feby Lestari; Herry Mulyono; Yossinomita Yossinomita (P3M POLITEKNIK NEGERI AMBON, 2025)
Generation Z plays a pivotal role in shaping contemporary trends, including those in the stock market. In the digital era, social media serves as a dominant medium for this demographic to access, discuss, and disseminate investment-related information. This study examines the influence of Generation Z in Jambi City on stock market trends through a statistical analysis of social media activities. Data were obtained from interactions on Instagram, YouTube, Twitter/X, Discord, TikTok, and Telegram, integrated with corresponding stock market indicators. The analysis employed classical assumption tests to assess the relationship between the intensity of Generation Z’s social media engagement and stock market fluctuations. The study also investigates the extent to which online sentiment, discussion frequency, and platform-specific engagement correlate with short-term market volatility. By bridging behavioral finance and digital communication analysis, the research aims to contribute to a deeper understanding of how technologically adept young investors influence capital market dynamics. The findings are expected to offer valuable implications for policymakers, financial educators, and market practitioners in adapting strategies to the evolving digital investment landscape. Keywords: Generation Z, Social Media, Stock Market Trends, Digital Investment Behavior, Behavioral Finance.